Academic Certificate Fraud Detection System Framework Using Blockchain Technology - Ninda Lutfiani; Desy Apriani; Efa Ayu Nabila; Juniar, Hega Lutfilah (IAIC Bangun Bangsa, 2022)
The era of rapid disruption was accompanied by increased crime in data falsification and interception. The philosophy of Blockchain technology is related to its ontology; it can be characterized, applied, and realized by how it works in the world of education. Blockchain technology is used to verify the authenticity of academic degrees and certificates. Systems that use digital signature schemes and implementation timestamps in the development of blockchain technology use blockchain software. The impact of falsifying educational documents results in workers not being qualified for a particular position. The main interest of this service is to balance between graduates and employers by minimizing crime and falsifying educational documents. The method used in this research is a literature study from previous studies. As a result of maximizing the potential of blockchain technology, fees can also lead to checking the authenticity of certificates through trusted sources. The application and utilization of blockchain in the academy certificate fraud detection system can be a means of offering problems that exist from a global perspective and other stakeholders.